Existence results for Volterra-Stieltjes quadratic integral equations on an unbounded interval - Banas, Jósef (Mathematica Scandinavica, 2006)
We prove a few existence results for a nonlinear quadratic Volterra-Stieltjes integral equation on an unbounded interval. Our proof depends on suitable combination of the technique of measures of noncompactness and the Schauder fixed point principle. Such an approach permits us to obtain existence theorems under rather general assumptions.